INFLUENCE OF PRODUCT QUALITY AND BRAND IMAGE ON PURCHASE INTENTION “UNKL 347” CLOTHING PRODUCTS A STUDY ON BANDUNG WEST JAVA - Suganda, Uce Karna; Wardhana, Bayu Adhi; Oktavian, Rinaldi (CENTRAL ASIA AND THE CAUCASUS, 2022)
Now the creative industry business in the field of fashion is increasingly mushrooming, almost in all corners of the city of Bandung can be found with a variety of brands and themes. Along with the enactment of Law no. 22 of 1999 concerning regional autonomy which gives authority to each region to be able to manage its resources independently, the city of Bandung began to develop as a city that has great potential in its shopping tourism, with the realization of the determination of areas specifically developed for tourism activities that impact on the increase in the number of distributions, clothing and FO in the city of Bandung The objective of the research are to examine and analyze, influence product and brand image quality towards buying interest taken by the respondent. The analysis used an independent variable of product buying quality and brand image. The dependent variable is buying interest. The result of the research showed that product quality and brand imagestatistically positive and significant influential partial and simultaneous affect buying interest “UNKL 347” Clothing Bandung West Java.